Reliability analysis of mooring lines under corrosion and material degradation - Gomes Junior, Ricardo Soares (2020)
This work presents a procedure for reliability analysis of mooring lines under corrosion and material degradation over time. The proposed procedure is limited to the ultimate limit state (ULS) and considers mooring lines made up of chain and polyester rope segments, although the same methodology can be applied to steel wire segments. The weakest link concept is used to model the strength of a mooring line segment and simplified time-dependent probabilistic models for chain corrosion and polyester degradation are adopted to predict the strength degradation over time. The annual failure probability for different years is estimated by approximating the degraded strength by a piecewise constant model in order to perform a time invariant reliability analysis. A study case is presented, where annual extreme top tension is obtained from longterm statistics considering Brazilian offshore environmental conditions acting on a turret moored FPSO. The influence of chain corrosion rate and the number of virtual elements for polyester strength on the reliability analysis are studied. Finally, applications of this procedure for mooring line inspection planning and service life extension are explored.